2017
DOI: 10.1161/circulationaha.116.025349
|View full text |Cite
|
Sign up to set email alerts
|

Ranking Businesses and Municipal Locations by Spatiotemporal Cardiac Arrest Risk to Guide Public Defibrillator Placement

Abstract: Background Efforts to guide automated external defibrillator (AED) placement for out-of-hospital cardiac arrest (OHCA) treatment have focused on identifying broadly defined location categories without considering hours of operation. Broad location categories may be composed of many businesses with varying accessibility. Identifying specific locations for AED deployment incorporating operating hours and time of OHCA occurrence may improve AED accessibility. We aim to identify specific businesses and municipal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…Determining where to place AEDs in strategic downtown locations can be challenging. Sun et al 25 sought to identify locations in the city of Toronto for potential AED placement by assessing spatiotemporal cardiac arrest risk at these locations. By using the Toronto Regional RescuNET Epistry cardiac arrest database, they found that coffee shops and bank machines from the 5 largest Canadian banks occupied 8 of the top 10 locations in Toronto.…”
Section: Resuscitation and Response To Cardiac Arrestmentioning
confidence: 99%
“…Determining where to place AEDs in strategic downtown locations can be challenging. Sun et al 25 sought to identify locations in the city of Toronto for potential AED placement by assessing spatiotemporal cardiac arrest risk at these locations. By using the Toronto Regional RescuNET Epistry cardiac arrest database, they found that coffee shops and bank machines from the 5 largest Canadian banks occupied 8 of the top 10 locations in Toronto.…”
Section: Resuscitation and Response To Cardiac Arrestmentioning
confidence: 99%
“…Consequently, much effort has focused on implementing public access defibrillator (PAD) programs and developing guidelines for strategic AED placement, which recommend AEDs be placed in high-risk areas and be easily reachable within a few minutes [7,8]. Prior research has focused on quantifying OHCA risk in different location types in cities worldwide, demonstrating generalizability of many of the findings [3,6,[9][10][11][12][13][14]. For example, transportation and recreation facilities have been established in multiple studies as high-risk areas that can benefit from AED placement [3,6,9,15].…”
Section: Resultsmentioning
confidence: 99%
“…A study on specific locations for AED deployment in Canada identified spatiotemporally better areas (e.g. coffee shops or banks) to cover OHCAs in public locations [26]. Therefore, further deployment of public-access AEDs and CPR training for staff in such high-risk areas is warranted to shorten the time to shock and improve outcomes after OHCA.…”
Section: Discussionmentioning
confidence: 99%